Additive and subtractive manufacturing of composites - Mavinkere Rangappa, Sanjay; Gupta, Munish Kumar; Siengchin, Suchart; Song, Qinghua (Professor of mechanical engineering) (Springer series in advanced manufacturing., 2021)
This book describes crucial aspects related to the additive and subtractive manufacturing of different composites. The first half of this book mainly deals with the various types of composite fabrication methods along with the introduction, features and mechanisms and also the processing of composite materials via additive manufacturing route. Also, the thermal, mechanical, physical and chemical properties relevant to the processing of composite materials are included in the chapters. The second half of this book primarily demonstrates an extensive section on the different types of additive manufacturing processes like selective laser sintering, selective laser melting, stereolithography, fused deposition modeling and material jetting used to fabricate the metals and polymers. Also, the chapters address the complete description of fabrication processes for metal matrix composites and polymer matrix composites. Moreover, the different methods adopted such as short peening, micro-machining, heat-treatment and solution treatment to improve the surface improvement are well discussed. This book gives many helps to researchers and students in the fields of the additive and subtractive manufacturing of different composites.